Methodological instructions for practical works in the "Computer circuitry" academic discipline - Skorodielov, Volodymyr Vasyliovych; Heiko, Hennadii Viktorovych; Lipchanska, Oksana Valentinivna (National technical university "Kharkiv polytechnic institute", 2024)
«Computer circuitry» is one of the fundamental disciplines in the field of «Computer Engineering», which provides theoretical and engineering training necessary for the implementation of scientific research and practical work on the research, development and operation of computer hardware, embedded microprocessor and microcontroller systems, computer systems and networks for various purposes (information, medical and industrial). As a result of studying the discipline, students should know: the element base of computers (digital integrated circuits of hard and programmable logic with varying degrees of integration), the principles of building on their basis typical functional units of digital devices of computers, microprocessor and microcontroller systems.
Keywords: methodological instructions; information technololy; flip-flops; counters; multiplexers; adders; designing digital devices